Pengaruh E-wallet Service Dimensions Terhadap Customer Loyalty yang Dimediasi oleh Customer satisfaction - Putri, Fakhirah Febriana; Soepatini, Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates how various aspects of e-wallet services influence Customer Loyalty, with customer satisfaction serving as a mediating factor. A quantitative causal approach was employed, involving seven research variables: five independent variables Service Quality, Ease of Use, Usefulness, Cost, and security; one dependent variable, Customer Loyalty; and one intervening variable, customer satisfaction. The sample consisted of 250 students in Surakarta who had been using e-wallets for at least three months, collected through an online questionnaire using purposive sampling. Data were analyzed using PLS-SEM via SMARTPLS 3, including assessments of the measurement model (outer model) and structural model (inner model) to evaluate validity, reliability, multicollinearity, and hypothesis testing for both direct and mediating effects. The results reveal that all service dimensions have positive and significant effects on both customer satisfaction and loyalty, while customer satisfaction significantly mediates the relationship between service dimensions and loyalty. These findings highlight the importance of enhancing Service Quality, Ease of Use, Usefulness, Cost efficiency, and security as strategies to strengthen e-wallet user loyalty.